TEACHING SEWING TECHNIQUES TO STUDENTS WITH DISABILITIES - Jamoliddinova Makhbuba Sotvoldiyevna (Western European Studies, 2024)
This research focuses on the inclusive approach of teaching sewing techniques to students with disabilities. Sewing, as a practical and creative skill, offers numerous benefits, including enhanced fine motor skills, cognitive development, and selfesteem. The study investigates effective teaching methods, adaptive tools, and customized instructional strategies that cater to the diverse needs of students with disabilities in the context of sewing education. By adopting an inclusive and accommodating approach, educators can empower students with disabilities to develop essential life skills and foster a sense of independence through the art of sewing
Keywords: Inclusive Education; Sewing Techniques; Adaptive Teaching